Excel in calculus using calculator / Mohd Syafiq Abdul Rahman and Ahmad Rashidi Azudin - Abdul Rahman, Mohd Syafiq; Azudin, Ahmad Rashidi (Unit Penerbitan JSKM, 2020)
Calculus is one of the branches of mathematics that all engineering students at UiTM should take in their Diploma level. In UiTM, the code for the course of Calculus I is MAT183. Calculus I is very important as this subject prepares them basic skills to study further calculus in a higher level. For MAT183, there are 5 chapters in the syllabus. The chapters covered are Limits, Differentiations, Application of Differentiations, Integration and Applications of Integrations.